Biomechanical analysis of likelihood of optic canal damage in peri-orbital fracture. Issue 1 (1st January 2018) - Nagasao, Tomohisa; Morotomi, Tadaaki; Kuriyama, Motone; Tamai, Motoki; Sakamoto, Yoshiaki; Takano, Naoki
Abstract: Purpose: Detection of optic canal fractures is often difficult because of the subtleness of the fracture. If we could clarify impact on which region around the orbit is likely to accompany the fracture of the optic canal, the knowledge should be useful to make early diagnosis of optic canal fractures. The present study was conducted to elucidate this issue. Methods: Ten finite element models were produced simulating the skulls of ten humans (8 males and 2 females; 43.8 ± 10.2 y/o). The peri-orbital area of each of the ten models was divided into eight regions in a clockwise fashion per 45 degrees. These regions were defined as Superior-Medial (0–45 degrees), Medial-Superior (45–90 degrees), Medial-Inferior (90 to 135 degrees), Inferior-Medial (135 to 180 degrees), Inferior-Lateral (180–225 degrees), Lateral-Inferior (225 to 270 degrees), Lateral-Superior (270–315 degrees), and Superior-Lateral regions (315–360 degrees), respectively. Dynamic simulation of applying traumatic energy on each of these regions was conducted. Resultant fracture patterns were evaluated using finite element analyses. Thereafter, frequencies of fracture involvement of the optic canal were evaluated for each of the eight regions. Results: The involvement of the optic canal was most frequent for the Superior-Medial region (7/10), followed by the Medial-Superior region (5/10). Conclusion: Optic canal fracture is likely to occur when the area between the supra-orbital notch and the medial canthus are strongly impacted. When evident fracture or serious damage of soft tissue is observed in this area, occurrence of optic canal fracture should be suspected.